Ultrasound induced fluorescence of nanoscale liposome contrast agents - Zhang, Qimei; Morgan, Stephen P.; O’Shea, Paul; Mather, Melissa L. (Public Library of Science, 2016)
A new imaging contrast agent is reported that provides an increased fluorescent signal upon application of ultrasound (US). Liposomes containing lipids labelled with pyrene were optically excited and the excimer fluorescence emission intensity was detected in the absence and presence of an ultrasound field using an acousto-fluorescence setup. The acousto-fluorescence dynamics of liposomes containing lipids with pyrene labelled on the fatty acid tail group (PyPC) and the head group (PyPE) were compared. An increase in excimer emission intensity following exposure to US was observed for both cases studied. The increased intensity and time constants were found to be different for the PyPC and PyPE systems, and dependent on the applied US pressure and exposure time. The greatest change in fluorescence intensity (130%) and smallest rise time constant (0.33 s) are achieved through the use of PyPC labelled liposomes. The mechanism underlying the observed increase of the excimer emission intensity in PyPC labelled liposomes is proposed to arise from the “wagging” of acyl chains which involves fast response and requires lower US pressure. This is accompanied by increased lipid lateral diffusivity at higher ultrasound pressures, a mechanism that is also active in the PyPE labelled liposomes.